2020
DOI: 10.3390/socsci10010003
|View full text |Cite
|
Sign up to set email alerts
|

Brothels as Sites of Third-Party Exploitation? Decriminalisation and Sex Workers’ Employment Rights

Abstract: Decriminalisation is arguably essential to protecting the human rights of sex workers. Nonetheless, there are suggestions that decriminalisation has less influence on sex workers’ experiences of working than many assume. This paper explores management practices in brothels in the context of decriminalisation in New Zealand, focusing on sex workers’ employment status, managerial control and agency. We interviewed 14 brothel operators and 17 brothel-based sex workers in this study. The findings suggest that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Within the New Zealand context, sex work which is carried out indoors, working by appointment and at a low-volume is often constructed as the ‘best’ or most acceptable way of working (Easterbrook-Smith, 2021a). In many cases work perceived as more socially acceptable is still in managed brothels, despite observations from researchers in New Zealand that managed work can still be a site of exploitation, while private (self-managed) work permits greater autonomy and ability to decline clients (Abel and Fitzgerald, 2012; Abel and Ludeke, 2021).…”
Section: Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Within the New Zealand context, sex work which is carried out indoors, working by appointment and at a low-volume is often constructed as the ‘best’ or most acceptable way of working (Easterbrook-Smith, 2021a). In many cases work perceived as more socially acceptable is still in managed brothels, despite observations from researchers in New Zealand that managed work can still be a site of exploitation, while private (self-managed) work permits greater autonomy and ability to decline clients (Abel and Fitzgerald, 2012; Abel and Ludeke, 2021).…”
Section: Existing Literaturementioning
confidence: 99%
“…In media coverage, the owners of what I term low-volume brothels sometimes emphasise their workers see fewer clients than workers in other establishments (McCarthy, 2015; Meadows, 2014). Low-volume agencies typically charge more per appointment or period of time, and often advertise an all-inclusive ‘girlfriend experience’ service for this comparatively higher price, while at other brothels, workers are more likely to negotiate extra services with individual clients (Zangger, 2015; Abel and Ludeke, 2021; Easterbrook-Smith, 2021a).…”
mentioning
confidence: 99%
“…The initiators exploited female managers by negatively targeting their social status, personal life, relationships and physical appearance. The superiors were found to exploit female managers through social media by professional discredit and emotional bullying creating abusive work conditions (Abel and Ludeke, 2021).…”
Section: Negative Use Of Social Media Against Female Managersmentioning
confidence: 99%
“…(Sophie) This experience described by Sophie echoes the findings of other recent research with sex workers who work in managed environments. Abel and Ludeke (2021) found that while challenges certainly remained for brothel-based sex workers, decriminalisation has provided an environment in which there is increased scope for sex workers to experience working conditions that are safer and more supported than they are when aspects of sex work are criminalised.…”
Section: Autonomy Harms: Freedom and The Power To Choosementioning
confidence: 99%